Kennings: Riddles of Metonymy or Metaphor? - Broz, Vlatko (2008)
The famous figures of speech permeating Beowulf are well known to all scholars of English Historical Linguistics, but they are certainly not receiving their due attention. Kennings have been considered as idiosyncratic metaphors of Old Germanic poetry (Marquardt 1938, Gardner 1969) that are very difficult to understand because of a rather enigmatic way of making reference to people or things (Brodeur 1960, Wehlau 1997). How exactly can we work out the meaning of the compounds seġ l-rā d 'sail-road' and hwæ ; l-weġ 'whale-way' both denoting the noun ‘ sea’ without relying on glossaries or footnotes of Old English textbooks? Now that semantics has come into the spotlight due to the success of Cognitive Linguistics, it may be an interesting idea to take a look at how kennings could be deciphered using the tools and the theoretical framework of the most propulsive movement in linguistics today. Cognitive Linguistics all too often stresses that metaphors and metonymies are ubiquitous in everyday use of language and not merely figures of poetic language (Lakoff & Johnson 1980:3-6) The semantic underlying processes that determine our categorization of the world are reflected in language, so metaphorical expressions should not be treated in isolation, but as linguistic realisations of conceptual metaphors. This paper will show how different the conceptual metaphors identifiable in the kennings of Beowulf are from those that we use today. For example, the fixed poetic formulas such as bā ncofa ‘ bone-chamber’ , bā nfæ ; t ‘ bone-container’ or bā nhū s ‘ bone-house’ all mean ‘ body’ . Several cognitive mechanisms are at work here: containment image schema which gives rise to conceptual metaphors such as BODY IS CONTAINER (Lakoff 1987), which is combined with the PART FOR WHOLE metonymy (a.k.a. synecdoche), bone being the essential part of the whole, i.e. body. The paper will also raise questions how reliable such an analysis is, if we take into account the fact that Old English is a dead language and that the world of Anglo-Saxons and their culture is not so readily accessible to us. It will also be a good test to see whether the cognitive theory metaphor can be applied in a diachronic perspective.
Projekt MZOS
ENG